Digital sovereignty of physical education teachers in Germany: a situation analysis (2017–2021) on the gap between educational policies and practical implementation in further physical education teacher trainings - Berkel, Fides; Bohm, Daniël; Wulff, Hagen; Reith, Gabriel; Wendeborn, Thomas (Frontiers in Education, 2025)
The increasing digitalization of society, particularly in education, requires both institutions and individuals to develop necessary structures and competencies for a confident participation in the digital world, a concept defined as digital sovereignty. Physical education (PE) teachers’ digital literacy is crucial to address the challenges of digitalization and this is to be developed with further PE teacher trainings. Therefore, this study investigates the integration of content on digitalization in further PE teacher trainings across Germany between January 2017 and May 2021. To address the question how digitalization-related content is represented in the further PE teacher trainings, a total dataset of 6,326 further PE teacher trainings involving 48,540 teachers was analyzed. The SEPACK.digital model was used as the theoretical framework in order to underpin PE-related issues from a perspective of content knowledge and to position the digital world as a global media phenomenon. The analysis shows a wide variation in representative digitalization-related content available in the German federal states. Further qualitative content analysis categorized the content in three stages into content with or without reference to digitalization, digitalization-related aspects and movement fields. The systematic and category-based approach allows for the content of further PE teacher trainings to be systematized and conclusions to be drawn to answer the research questions. Four of 12 German federal states did not offer any digitalization-related further teacher trainings at all, while the others offered further PE teacher trainings on digitalization with a share of 0.6 to 4.6. This reveals that most digitalization-related content focused on the functional use of media, such as video analysis. Only little emphasis is placed on the development of digital competencies or the personal-reflective dimension of digitalization. As a result, the study identifies the limited inclusion of digital content in further PE teacher trainings and following insufficient digital competencies among PE teachers. This result can be further emphasized by considering the significant disparity among the German federal states. Additionally, the study identifies a significant gap between the objectives of federal educational policies and the actual implementation of digital education in further PE teacher trainings. The findings suggest that further PE teacher trainings are largely inadequate in addressing the transformative potential of digitalization. Further teacher training is crucial for developing digital competencies among PE teachers and aligning their skillset with the demands of students’ increasingly digitalized life. Recommendations are consequently made for developing more targeted and comprehensive further PE teacher trainings, emphasizing both the practical and the critical reflection of digital media in PE. The study thereby contributes to the academic discourse by highlighting the necessary link between policy initiatives and subject-specific approaches to digital competencies in PE to develop evidence-based further PE teacher trainings.